Estimate of Revenue Foregone on Customs Duty in Bangladesh - World Bank (World Bank, Washington, DC, 2018)
This note is a preliminary estimate of the revenue foregone under customs duty because of the various exemptions provided on imports. The estimates are intended as an input into the policy process that seeks to balance revenue raising measures, trade and tariff policy, and competitiveness. The estimates are preliminary because of data limitations. While the size of the revenue foregone can be roughly estimated, data on the reason for the exemptions was not available. Thus, targeted policy recommendations cannot be provided at this stage.